A confirmatory factor analysis on task-technology fit for a student portal - Norshidah, Mohamed; Muna Azuddin; Nor, Shahriza Abdul Karim; Ramlah Hussein, * (2011)
This research seeks to identify the predictors of task-technology fit in the context of student portal. The population comprises undergraduate students who are registered and active at three faculties in a public institution of higher learning in Malaysia. The sample is 570 students drawn using cluster sampling approach based on courses offered according to the level of study at each faculty. The study adapted six measures from past e-commerce study and found five predictors of task-technology fit.